Replication Data for "COVID-19 and Rural Livelihoods: Lessons from a Longer-Term Assessment in Guatemala" - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The dataset comprises a panel of 1,262 agricultural households from 86 communities across the departments of Huehuetenango, Quiché, and San Marcos in Guatemala. These households were first surveyed in person in November December 2019 (baseline) and subsequently by phone in follow-up rounds conducted in May June 2020, 2021, and 2022 to assess the impacts of COVID-19 on rural livelihoods and food security. The baseline survey collected detailed information on household socioeconomic characteristics, food security, dietary diversity, migration attitudes, and other economic and financial indicators. The follow-up rounds tracked changes in selected economic, nutritional, and food security outcomes over the three years following the COVID-19 outbreak, while also capturing the effects of additional shocks such as extreme weather events. An additional round was conducted in November December 2022 with a subsample of 777 households, replicating the baseline survey to allow for direct comparisons.